(untitled) (Revista científica Olimpia, 2015)
The present work exposes the essential elements of the volitional preparation in athletes of boxing of the school category with the objective of continuing perfecting the components of this preparation, the same one constitutes an indispensable element as part of the general, given psychological preparation the characteristics and difficult and exceptional conditions in that a boxer is unwrapped. They offer recommendations that guide tasks of psychological character to conceive the volitional preparation in boxing athletes.